Media dan Hibrid Identitas Keagamaan di Era Digital - Lailatur Rofidah; Abdul Muhid (Jurnal Dakwah dan Komunikasi, 2022)
Digital Era is an era where a shift process come up from industrial based to an information technology using computer or other technology devices as medium or communication. It gives benefit to preacher which various Islamic Ideologies background. The internet has a significant influence to millennial generation and Z generation. The increasing number of Islamic identities that are spread in online media can have an effect on forming religious hybridity among Y and Z generations. This study aims to answer whether online media has an effect on forming religious hybridity among Y  and Z generations. The research method used is literature review, data obtained from previous research, research keywords become references to find data. This study found that online media has a major influence in shaping religious hybridity among millennial and Z generation. This can be seen from the high use of online media among millennial and Z generation and they often look for religious issues through online media. This is also supported by the effect of da'wah in online media that comes from various religious identities. This study concludes that online media has a major influence in shaping religious hybridity among the millennial generation and Z generation.